2001
DOI: 10.1183/09031936.01.17408020
|View full text |Cite
|
Sign up to set email alerts
|

The role of positron emission tomography with 18 F-fluoro-2-deoxy-D-glucose in respiratory oncology

Abstract: In the past 5 yrs, positron emission tomography (PET) with18F-fluoro-2-deoxy-d-glucose (FDG) has become an important imaging modality in lung cancer patients. At this time, the indication of FDG-PET as a complimentary tool to computed tomography in the diagnosis and staging of non-small cell lung cancer has gradually gained more widespread acceptance and also reimbursement in many European countries.This review focuses on the data of FDG-PET in the diagnosis of lung nodules and masses, and in locoregional and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(31 citation statements)
references
References 156 publications
1
28
0
2
Order By: Relevance
“…FDG-PET proved to be significantly more accurate than CT in locoregional LN staging. In the distinction between presence (N2-N3) or absence (N0-N1) of mediastinal LN disease, an overall sensitivity of 89% (67-100), a specificity of 92% and an accuracy of 90% (78-100) can be expected for FDG-PET, in contrast with a sensitivity of 65% , a specificity of 80% , and an accuracy of 75% (52-79) for CT [21]. The superiority of FDG-PET can be explained by the fact that the size of LNs on CT is a relative criterion; FDG-PET correctly identifies small malignant nodes and large benign nodes.…”
Section: Locoregional Lymph Node Stagingmentioning
confidence: 97%
See 3 more Smart Citations
“…FDG-PET proved to be significantly more accurate than CT in locoregional LN staging. In the distinction between presence (N2-N3) or absence (N0-N1) of mediastinal LN disease, an overall sensitivity of 89% (67-100), a specificity of 92% and an accuracy of 90% (78-100) can be expected for FDG-PET, in contrast with a sensitivity of 65% , a specificity of 80% , and an accuracy of 75% (52-79) for CT [21]. The superiority of FDG-PET can be explained by the fact that the size of LNs on CT is a relative criterion; FDG-PET correctly identifies small malignant nodes and large benign nodes.…”
Section: Locoregional Lymph Node Stagingmentioning
confidence: 97%
“…Based on 12 well-designed prospective studies, it can be concluded that FDG-PET has proven to be accurate in differentiating benign from malignant lesions as small as 1 cm [21]. An overall sensitivity of 96% (range 83-100), specificity of 79% (52-100) and accuracy of 91% (86-100) can be expected.…”
Section: Diagnosis Of Solitary Lung Nodule or Massmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent months the European Respiratory Journal has published a series of articles on advances in imaging [1][2][3][4][5][6][7][8]. These articles have reviewed the current role of imaging in the diagnosis and management of various airway and pulmonary diseases and have highlighted potential areas of research.…”
mentioning
confidence: 99%